Evaluation of asbestos exposure resulting from simulated application of spiked talcum powders. (6th December 2022) - Miller, Eric W.; Roberts, Benjamin; Keeton, Kara; Monnot, Andrew; Tarpey, Taylor; Zoghby, Nicole; Segrave, Alan; Pierce, Jennifer S.
Abstract: This study characterizes airborne asbestos exposures resulting from the adult application of cosmetic talc body powders spiked with known concentrations of tremolite. Raw talc ores were spiked with 0.005% and 0.1% asbestiform or non-asbestiform tremolite. Personal samples were collected during 16 simulated events, including puff and shaker application and associated clean-up activities. Airborne fiber levels (PCM) were not significantly different for simulations involving talc spiked with asbestiform and non-asbestiform tremolite ( p = 0.6104). For application and clean-up of talc spiked with 0.005% asbestiform tremolite, 2 of 24 (8.3%) samples were above the LOD for TEM (0.003 f/cc). For application of talc spiked with 0.1% asbestiform tremolite, 21 of 24 (87.5%) were above the LOD for TEM. The corresponding mean PCME asbestos concentrations were 0.016 f/cc for puff and shaker for samples collected in the first 15 min, 0.002 f/cc for puff and 0.004 f/cc for shaker in the second 15 min, and 0.005 f/cc for puff and 0.013 f/cc for shaker for the full 30 min. Mean PCME concentrations for samples collected during clean-up following application of talc spiked with 0.1% asbestiform tremolite were 0.003 f/cc for samples collected in the first 15 min following puff application, 0.005 f/cc for samples collected in the second 15 min following shaker application, and 0 f/cc for the remaining clean-up samples. Using the EPA's exposure factors, we determined the range of cumulative asbestiform fiber exposures that would result from product use, assuming asbestiform tremolite was present at 0.1%.